2021
DOI: 10.1111/cas.14885
|View full text |Cite
|
Sign up to set email alerts
|

The ALK inhibitors, alectinib and ceritinib, induce ALK‐independent and STAT3‐dependent glioblastoma cell death

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…On similar lines, CDK2 promotes cancer progression and resistance to radiotherapy (Wang et al, 2016). Alectinib and ceritinib, ALK inhibitors, have demonstrated cell‐killing effects in glioblastoma (Kawauchi et al, 2021). In summary, all three targets have been implicated in GBM pathology and developing novel, preferentially selective inhibitors of these kinases makes perfect therapeutic sense.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On similar lines, CDK2 promotes cancer progression and resistance to radiotherapy (Wang et al, 2016). Alectinib and ceritinib, ALK inhibitors, have demonstrated cell‐killing effects in glioblastoma (Kawauchi et al, 2021). In summary, all three targets have been implicated in GBM pathology and developing novel, preferentially selective inhibitors of these kinases makes perfect therapeutic sense.…”
Section: Resultsmentioning
confidence: 99%
“…As seen from Table 4, hits F 2 and F 7 were selected for further computational screening for potential molecular targets using SwissTargetPrediction (Gfeller et al, 2013) demonstrated cell-killing effects in glioblastoma (Kawauchi et al, 2021). In summary, all three targets have been implicated in GBM pathology and developing novel, preferentially selective inhibitors of these kinases makes perfect therapeutic sense.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…type="uri"> receptor , the insulin receptor, and the serine/threonine protein kinase STK22D (TSSK1). 59 The compound had been found to display growth inhibition and cellular toxicity of tumor cells, which may be dependent on its strong inhibition of ALK and other kinases; 72 ceritinib’s cytotoxic mechanism of action may, in fact, be due to its polypharmacology, 73 74 to which CD39 inhibition might additionally contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Kawauchi et al [44] demonstrated the anticancer activity of alectinib and ceritinib against U87MG, LN229, and GSC23 GBM cell lines. ALK inhibitors effectively induced GBM cell death and inhibited STAT3, causing caspase-dependent/independent cell death when administered alone.…”
Section: Crizotinib Alectinib and Ceritinibmentioning
confidence: 99%
“…AXL phosphorylation leads to PI3K and AKT activation. The Gas6/AXL/PI3K/Akt axis protects cells from apoptosis by S6K activation and BCL-2 phosphorylation [44]. AXL is widely expressed in GBM, and its biologically active form Phospho-AXL (P-AXL) is associated with poor prognosis [48].…”
Section: Axl Inhibitorsmentioning
confidence: 99%